Relationship Between Spirituality And Stress Of Parents Who Have Children With Congenital Disorders Treated In RSUP. H. Adam Malik Medan - Devi Ardila (Journal of Midwifery and Nursing, 2020)
The birth of a baby with congenital abnormalities can cause various problems in the family, especially parents. Problems that often occur in the form of feelings of depression or stress. One way that parents do to deal with stress is to pray and tell stories to others. This study aims to identify the relationship between spirituality and stress of parents who have children with congenital disorders who are treated at H. Adam Malik Hospital Medan by using a descriptive correlation design, sampling using the Accidental Sampling technique. The sample size obtained is 31 people. The research instrument was a questionnaire that included demographic data and statements about parental spirituality and stress. Data collection took place from April to May 2012. The results showed that parents have high spirituality (83.9%) and have low stress (51.6%) and there is a relationship between spirituality and stress of parents who have children with congenital disorders who are treated at the RSUP. H. Adam Malik Medan with weak relationship strength with negative pattern (p=0.043, r= -0.366). This means that the higher the spirituality of parents, the lower the stress of parents who have children with congenital disorders who are treated at H. Adam Malik Hospital Medan. The recommendation for further research is to conduct further research on the relationship between spirituality and stress of parents who have children with congenital disorders with a larger number of respondents. 6%) and there is a relationship between spirituality and stress of parents who have children with congenital disorders who are treated at the RSUP. H. Adam Malik Medan with weak relationship strength with negative pattern (p=0.043, r= -0.366). This means that the higher the spirituality of parents, the lower the stress of parents who have children with congenital disorders who are treated at H. Adam Malik Hospital Medan. The recommendation for further research is to conduct further research on the relationship between spirituality and stress of parents who have children with congenital disorders with a larger number of respondents. 6%) and there is a relationship between spirituality and stress of parents who have children with congenital disorders who are treated at the RSUP. H. Adam Malik Medan with weak relationship strength with negative pattern (p=0.043, r= -0.366). This means that the higher the spirituality of parents, the lower the stress of parents who have children with congenital disorders who are treated at H. Adam Malik Hospital Medan. The recommendation for further research is to conduct further research on the relationship between spirituality and stress of parents who have children with congenital disorders with a larger number of respondents. This means that the higher the spirituality of parents, the lower the stress of parents who have children with congenital disorders who are treated at H. Adam Malik Hospital Medan. The recommendation for further research is to conduct further research on the relationship between spirituality and stress of parents who have children with congenital disorders with a larger number of respondents. This means that the higher the spirituality of parents, the lower the stress of parents who have children with congenital disorders who are treated at H. Adam Malik Hospital Medan. The recommendation for further research is to conduct further research on the relationship between spirituality and stress of parents who have children with congenital disorders with a larger number of respondents.